In situ preparation of hierarchically porous β-tricalcium phosphate bioceramic scaffolds by the sol-gel method combined with F127. Issue 5 (1st April 2020) - Zhang, Jinran; Zhou, Jian; Huang, Xiaoguang; Wang, Lin; Liu, Guizhen; Cheng, Jiping
Abstract: A hierarchically porous β-tricalcium phosphate (β-TCP) bioceramic scaffold was prepared by in situ foaming using the sol-gel method, and a nonionic surfactant Pluronic F127 (EO99 PO65 EO99 ) was used as the template. The average size of the connecting macropores in the scaffolds increases in the range of 200–500 μm as the amount of the surfactant F127 decreases. The size of micropores on the scaffold wall is between 0.5 and 5 μm, and the microporosity reduces with an increase in the sintering temperature. In addition, the morphology of grains is rough and contains 3-10-nm nanopores and nanoscale "groove" pores due to the removal of F127 as a "soft templating" material. Finally, immersion experiments with simulated body fluids (SBF) in vitro showed that the scaffold had good bioactivity. The hierarchically porous β-TCP bioceramic prepared by this method has the advantages of low cost and a simple process; thus, this material is ideal for repairing bone defects in orthopaedics.